The cytotoxic effect of Vincristine-Amygdalin combination on human cervical cancer cell line (Hela cancer cell line) - Jumaa, Azal H. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Resistance of cancer cells toward chemotherapeutics drugs is considered as the major problem of cancer treatment. One of the strategies that are used to overcome cancer cells resistance to anticancer drugs is the drugs combination. Vincristine and amygdalin combination was used in this study to identify the possibility of synergistic effect between them as anticancer, which is mainly due to unrelated mechanism of action for vincristine and amygdalin. The result of the study demonstrate that the cytotoxic effect of (vincristine and amygdalin) combination was significantly more than the cytotoxicity of each one alone on Hela cancer cell line (human cervical cancer cell line). The result shows also the cytotoxicity of (vincristine and amygdalin) combination increases with the increase in the concentration which ranged between (1-10000) µg/ml, beside the increase in the incubation periods which are (24, 48 and 72) hours.